Design of a multi-band antenna for GNSS application - Ang, Jason Song Pek (2018)
Global Navigation Satellite System (GNSS) has been a popular topic for many years in wireless communication. For this project, it has been developed for navigating the location using a Global Positioning System (GPS). This final year project aims to apply the knowledge of antenna theory to solve the challenge faced in antenna design. In various design, the antenna design consists of one S-shaped slot patch, air, two dielectric substrates for top and bottom, ground plane and a microstrip line. The radiating patch is attached in order to improve the circular polarization for two frequency bands and enhance the radiation pattern. This antenna was designed with a single feed which reduces antenna cost. This proposed antenna is constructed using High-Frequency Structural Simulator (HFSS). A parametric analysis is done by using an optimization toolbox in HFSS to achieve higher antenna performance. The return loss recorded at the lowest point was around -4.85dB at 1.227 GHz for lower frequency band and -11.59dB at 1.575 GHz for the upper frequency band. The highest value of gain for the lower band (1.227 GHz) and upper band (1.575 GHz) are around at 7.01dB and 3.05dB. The measured axial ratio for the lower band at 1.227 GHz and upper band at 1.575 GHz are 2.40dB and 1.25dB. In this project, the various design factors were antenna parameters, type of substrate materials used, feeding scheme and dimensions of the antenna that were studied in the literature review. Besides designing an antenna and running the simulations, the results obtained would be also discussed and analyzed.